Relationship between Vitamin C and Parathyroid Hormone and Insulin Resistance Associated with Obesity - Ali Mojed Al-Dhmoshy (Journal of Global Pharma Technology, 2017)
Objective: To show the association between parathyroid hormone and obesity and to determine the relationship between vitamin C and insulin resistance with obesity. Background Obesity is representing a global epidemic that affecting more than 1.9 billion adults in 2014, 18 years and older, were overweight. Of these over 600 million were obese. Many causes have been implicated for developing obesity such as: environmental, hereditary, medical disease like endocrine disorders furthermore, some medication like antipsychotic drugs and steroids. Obese people are at high risk to develop much complication such as diabetes, hypertension, atherosclerosis, joints problems, cancers especially hormone dependent, respiratory problems and others. Material and methods: Eighty-eight people were in cladding this study visiting Merman medical city from December 2015 to June 2016.A 40 normal non-obese , and 48 obese, The overall mean age of patients and controls was 34.48±9.83 and 28.78±6.96 years old, respectively. They were classified according to body mass index after measuring their weight, height, The be line Questionnaire was done for all patients and control for diagnosis excluded disease and any treatment that effect on obesity. The investigation was done and include fasting blood glucose, Calcium , Phosphate, HOMA IR, Vitamin C, Then hormonal testing : parathyroid hormone, insulin hormone, c-peptide . Results: There is a significantly higher difference (p value ≤ 0.05) between case and control groups concerning education, gender. Regarding investigation there is significantly higher difference (p value ≤ 0.05) between case and control groups in parameters of fasting blood glucose, HOMA IR, but all the investigations were within normal acceptable clinical range. Whereas, in regard to the hormonal parameters:- parathyroid hormone : There is significant difference between case and control (p value ≤ 0.05) , While no significant difference (p value ˃ 0.05) in percentage between case and control for insulin hormone . While significant difference in C-peptide. Conclusion: The results of this study support the evidence that obesity associated with parathyroid hormone. Furthermore obese patients have a tendency toward higher serum PTH, there does not appear to bea resistance to PTH in the obese based on the similar serum calcium-PTH curve between obese and no obese. Hyperparathyroidism also can cause obesity. Vitamin C has responsible effect in preventing of obesity by antioxidant role.Keywords: Obesity, Vitamin C, Ascorbic acid, Parathyroid hormone, Hyperparathyroidism, Insulin resistance.